Rywalizacja strategiczna w cyberprzestrzeni i jej konsekwencje dla bezpieczeństwa międzynarodowego - Mirosław BANASIK; Lech CHOJNOWSKI (Przegląd Geopolityczny)
The purpose of the research was to clarify the mechanisms of strategic competition, including in cyberspace, and to identify the challenges and threats arising from it for international security. Literature analysis and criticism, non-participatory observation and case studies were used to solve the research problems. In the research process, it was determined that in the next decade the strategic competition will be most intense between the United States, and China and the Russian Federation. The biggest threats to the existing international order will be the ambitions of revisionist states related to territorial claims and expansion of spheres of influence. These states will use mainly non-military instruments of influence, including cyberspace, to gain an advantage over competing societies. Cyberspace will not only be the main pillar of competition, but also an alternative to it.